Neurons Dendrites and Axons - Emiliano Aranda Abreu, Gonzalo; Elena Hernández Aguilar, María (IntechOpen, 2019)
The brain is the most complex structure that exists in the universe, consisting of neurons whose function is to receive information through dendrites and transmit information through the axon. In neurosciences one of the main problems that exists are neurodegenerative diseases for which until now there has been no cure. This book is mainly focused on updating the information on the signaling process carried out in the development of axons. Topics such as axon guidance and its interaction with the extracellular matrix are discussed. Other important topics are semaphorins and their relationship with neurodegenerative diseases, and the neurobiology of the gap junction in the dorsal root ganglion. Finally, the topic of bioelectrical interfaces destined to regenerate damaged nerves is covered. The information in this book will be very important both for researchers who work with these issues and doctoral students who are involved in neuroscience.